PENGARUH MODEL PEMBELAJARAN TALKING CHIPS BERBASIS LESSON STUDY TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SD - Ni Nyoman Satriani (Universitas Pendidikan Ganesha, 2018)
The aims of this research is to know the significant influence learning model of Talking Chips based on lesson study towards the results of learning science of fourth grade students, group IV in Sukawati district, academic year 2017/2018. The design of this research is research of quasi experiment with nonequivalent control group design program. The sample of this research is all of the fourth grade students, group IV in Sukawati district as many as 145 students. The sample of this research is the fourth grade students of SDN 3 Batubulan Kangin as many as 40 students as experiment group and the fourth grade students of SDN 2 Batubulan Kangin as many as 40 students as control group. The data were collected by using objective test in multiple choice. The result of this research shows that the result of learning science by using learning model Talking Chips based on Lesson Study in the good category with average value 81,38 and the result of learning science by using conventional learning in the satisfactory category with average value 71. Based on the result of t-test analysis, there were obtained t value = 5,778 and t table = 1,991 so that t value= 5,778 > t table = 1,991 then Ho is rejected. It proves that there are significant difference in the results of learning science between group students which were taught by using learning model of Talking Chips based on Lesson study compared to the students which were taught by using conventional learning of fourth grade students, group IV in Sukawati district, academic year 2017/2018. Therefore, it can be concluded that the application of learning model Talking Chips based on Lesson study, influence the result of learning science of fourth grade students, group IV in Sukawati district, academic year 2017/2018.